Annex No. (1) to the Minister of Finance's Decree No. 310 of the Year 2013 Concerning the Determination of the Percentages, Commodities and Rentals to Which the System of Addition for Account of the Tax Apply in Accordance With the Provisions of Articles Nos. (59-Bis), (59-Bis-1) and (59-Bis-2) of the Income Tax Law Promulgated as Per Law No. 91 of the Year 2005and Its Amendment - Egypt (2025)
Annex No. (1) to the Minister of Finance's Decree No. 310 of the Year 2013 Concerning the Determination of the Percentages, Commodities and Rentals to Which the System of Addition for Account of the Tax Apply in Accordance with the Provisions of Articles Nos. (59-Bis), (59-Bis-1) and (59-Bis-2) of the Income Tax Law Promulgated as Per Law No. 91 of the Year 2005 and Its Amendment وزارة المالية ملحق رقم (1) لقرار وزير المالية رقم 310 لسنة ٢٠١٣ بتحديد النسب والسلع والإيجارات التي يسرى عليها نظام الإضافة تحت حساب الضريبة طبقا لأحكام المواد (59 مکرر)، (59 مکرر ۱)، (٥٩ مکرر ٢) من قانون الضريبة على الدخل الصادر بالقانون رقم 91 لسنة ٢٠٠٥ وتعديلاته